2020
DOI: 10.1371/journal.pone.0230981
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions of the autophagy-related proteins Atg4 and Atg8 in Cryptococcus neoformans

Abstract: Autophagy is a mechanism responsible for intracellular degradation and recycling of macromolecules and organelles, essential for cell survival in adverse conditions. More than 40 autophagy-related (ATG) genes have been identified and characterized in fungi, among them ATG4 and ATG8. ATG4 encodes a cysteine protease (Atg4) that plays an important role in autophagy by initially processing Atg8 at its C-terminus region. Atg8 is a ubiquitin-like protein essential for the synthesis of the double-layer membrane that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…To investigate the role of the core autophagy machinery genes (ATGs), we knocked out all 14 ATG genes in C. neoformans. Each single deletion mutant showed the expected autophagy phenotype, such as impaired growth and survival upon nitrogen starvation, as previously reported by other groups (Hu et al, 2008;Oliveira et al, 2016;Gontijo et al, 2017;Ding et al, 2018;Zhao et al, 2019a;Roberto et al, 2020). However, our results suggested that autophagy-related genes may also be involved in other cellular functions, such as maintaining the integrity of cell membranes.…”
Section: Discussionsupporting
confidence: 89%
“…To investigate the role of the core autophagy machinery genes (ATGs), we knocked out all 14 ATG genes in C. neoformans. Each single deletion mutant showed the expected autophagy phenotype, such as impaired growth and survival upon nitrogen starvation, as previously reported by other groups (Hu et al, 2008;Oliveira et al, 2016;Gontijo et al, 2017;Ding et al, 2018;Zhao et al, 2019a;Roberto et al, 2020). However, our results suggested that autophagy-related genes may also be involved in other cellular functions, such as maintaining the integrity of cell membranes.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, we found many genes involved in DNA repair, remodeling, and maintenance of chromatin structure as differentially expressed, thus suggesting that DNA damage was likely occurring in fungal cells, probably contributing to cell death. Whether the positively charged peptide directly causes DNA damage or the damage is rather an indirect effect of ROS accumulation, which at high levels is lethal for fungal cells ( Roberto et al, 2020 ) needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More than 40 autophagy-related (ATG) genes have been identified in fungi ( Roberto et al, 2020 ). Our transcriptomic analysis found that ATG3, ATG4, ATG7, ATG9 and ATG17 encoding genes were upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy does not play a role in mitochondrial inheritance in C. neoformans either. Nishimura et al have shown that disruption of ATG8 (responsible for the creation of the autophagosome vesicle membrane [ 38 ] and NUC1 (an endonuclease involved in mtDNA degradation) do not have an effect on the preferential inheritance of MAT a mtDNA inheritance in Cryptococcus [ 24 ] ( Table 1 ). Consistently, we found that a unilateral cross of wild type with either atg3 Δ or aif1 Δ mutant defective in autophagy-related E2-like conjugation enzyme and mitochondrial nuclease respectively yielded the same UMI pattern as a cross between two wild type partners.…”
Section: Factors Important For Uniparental Mitochondrial Inheritanmentioning
confidence: 99%